2016
DOI: 10.1063/1.4964357
|View full text |Cite
|
Sign up to set email alerts
|

Nano-scaled diffusional or dislocation creep analysis of single-crystal ZnO

Abstract: The nanoindentation time-dependent creep experiments with different peak loads are conducted on c-plane (0001), a-plane (112¯0) and m-plane (101¯0) of single-crystal ZnO. Under nano-scaled indentation, the creep behavior is crystalline orientation-dependent. For the creep on (0001), the stress exponent at low loads is ∼1 and at high loads ∼4. The stress exponents under all loads are within 3∼7 for the creep on (112¯0) and (101¯0). This means that diffusion mechanism and dislocation mechanism is operative for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Another recent application has been to investigate the strain hardening surrounding larger Rockwell indentations made in electrodeposited nanocrystalline nickel material with different grain sizes [40]. Additional examples include (1) investigating shear banding in metallic glass materials [41]; and, nano-probing of diffusion-controlled deformation on a copper crystal surface [42] and on different surfaces of ZnO crystals [43].…”
Section: Hardness As a Test Probementioning
confidence: 99%
“…Another recent application has been to investigate the strain hardening surrounding larger Rockwell indentations made in electrodeposited nanocrystalline nickel material with different grain sizes [40]. Additional examples include (1) investigating shear banding in metallic glass materials [41]; and, nano-probing of diffusion-controlled deformation on a copper crystal surface [42] and on different surfaces of ZnO crystals [43].…”
Section: Hardness As a Test Probementioning
confidence: 99%
“…Kucheyev et al studied the deformation behavior of a c-plane (0001) ZnO single crystal by nanoindentation at the micro-scale indentation depth of about 1000 nm, and found that the elastic–plastic-deformation transition threshold depends on the loading rate, with faster loading resulting in a larger threshold [ 35 ]. Lin et al studied the creep behavior with different loading rates on c-plane (0001), a-plane ( ) and m-plane ( ) ZnO single crystals by nanoindentation experiments, and found that the creep displacements increased with the increasing loading rate [ 36 ]. Fang et al studied the effect of strain rate on the hardness and Young’s modulus of ZnO thin films by nanoindentation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical reliability will determine the long-term stability and performance for many of the nanodevices [23]. Lin et al [34] investigated the nanoscale creep behavior of single-crystal ZnO because it is usually fabricated into low-dimensional piezoelectric devices. They found that creep strain is mainly controlled by the interfacial diffusion between the nanoindenter tip and the test sample.…”
Section: Introductionmentioning
confidence: 99%